2022
DOI: 10.1088/1361-6528/ac60dc
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence labelled XT5 modified nano-capsules enable highly sensitive myeloma cells detection

Abstract: Accurate diagnosis of cancer cells in early stages plays an important role in reliable therapeutic strategies. In this study, we aimed to develop fluorescence-conjugated polymer carrying nanocapsules (NCs) which is highly selective for myeloma cancer cells. To gain specific targeting properties, NCs, XT5 molecules (a benzamide derivative) which shows high affinity properties against protease-activated receptor-1 (PAR1), that overexpressed in myeloma cancer cells, was used. For this purpose, 1,2-distearoyl-sn-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Figure S4 showed that, compared with the FT-IR spectrum of AuMSN-N NPs, a new peak at 844 cm −1 (characteristic band of C−S for mPEG-TK) 33 appeared in the spectrum of AuMSN-PEG NPs after the decoration of mPEG-TK. After DSPE modification, a new peak at 1738 cm −1 (characteristic band of C�O for DSPE) 34 was observed in the spectrum of the Janus NPs. These results proved the successful modification of mPEG-TK and DSPE on the Janus NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S4 showed that, compared with the FT-IR spectrum of AuMSN-N NPs, a new peak at 844 cm −1 (characteristic band of C−S for mPEG-TK) 33 appeared in the spectrum of AuMSN-PEG NPs after the decoration of mPEG-TK. After DSPE modification, a new peak at 1738 cm −1 (characteristic band of C�O for DSPE) 34 was observed in the spectrum of the Janus NPs. These results proved the successful modification of mPEG-TK and DSPE on the Janus NPs.…”
Section: Resultsmentioning
confidence: 99%